“We are the time”. Expectations and requests of UNIBA students concerning the time bank of the University: an empirical research - Fornasari, Alberto (Studi sulla Formazione/Open Journal of Education, 2019)
The time bank is a solidarity institution in which services are exchanged without the intermediation of money. It is based on an equal exchange of hours based on the needs and, at the same time, on the resources of individuals. The time banks activate solidarity and social promotion and are placed in a perspective of prevention of social disadvantage. The University Time Bank encourages ethical action by strengthening the common spirit of solidarity, networking the experiences and knowledge of the academic community. This paper presents an empirical research (based on significant sample of 1956 students) to better understand their expectations regarding the University Time Bank (activated through a pilot case), which services they would exchange and offer, and highlights the nature, opportunities and difficulties related to its organization, starting from its main users: the students.